Formação continuada dos professores de educação física : avaliando uma experiência formativa - Silva, Bruno Vasconcellos (2017)
This research aims at evaluating a continuing formation experience of Elementary School Physical Education Teachers, developed by the schools in the city of Cariacica-ES in the year of 2015, mediated by the Researcher and the Teacher of the above-mentioned institution, as well as subsidized by collaborative and collective reconstruction principles. The accomplishment of such experience was motivated by the wish to promote a continuing formation in which the demands and needs related to the Teachers’ daily life were heard and discussed, and the participants, in a collective and collaborative way, could contribute with the process, rebuilding the proposal in the course of the meetings, promoting their know-how. In this dynamics, the Teacher/mediator fostered meetings listed by the other Teachers, therefore, those were also co- responsible for the development, contributing for the formation rethinking. The theoretical debate, which supports the ongoing research, was deepened through the elaboration of a conceptual map that submits a mishmash of concepts that emerge and are integrated around the continuing formation, namely: critical perspective in contrast with the rational/technical beliefs; epistemology of the practice; Teachers’ Knowledge; and the professionalization movement. The work analyzes the public policies regarding aspects, their concepts and importance, and also debates the national and municipal legal marks. The study is qualitative, interpretative and the closer approximation procedures to the field were the participant observations. Semi-structured interviews and field diary were also used. Through the evaluation, the Teachers’ understanding was sought from what has been projected in the experience mentioned. In general, the participant educators assure they could see themselves towards the continuing formation conduction, that is, this formation seemed to configure the Teachers’ authorship and leading roles. Besides that, dissonances were identified during this formative process that indicate difficult determinants to be overcome, such as the educational legislation itself, work conditions, as well as the fact of depending on the Teachers’ will.